Comparative Volatility Analysis of Gold and Bitcoin as Con-ventional and Digital Assets (2020–2025) (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study examines the comparative volatility of gold and Bitcoin over the period January 2020 to August 2025, using monthly data and employing descriptive statistics, the Augmented Dickey-Fuller (ADF) test, GARCH (1,1), and the Dynamic Conditional Correlation Generalized Autoregressive Conditional Heteroskedasticity (DCC-GARCH) model estimated with EViews 13. The results show that Bitcoin is characterized by extreme and persistent volatility, reflecting its speculative nature, whereas gold remains stable and functions as a conventional safe-haven asset. Correlation analysis indicates that the relationship between gold and Bitcoin is generally weak but dynamic, as the strength and direction of their co-movements change across different market conditions. These findings highlight the potential role of gold as a hedge and Bitcoin as a speculative diversifier, offering insights for portfolio diversification and risk management. These results also suggest that investors should carefully consider their risk tolerance and investment horizon when allocating assets between traditional and digital commodities.